The concept of recognition : a dialogue between Paul Ricoeur and Axel Honneth - Ferrari, María Luján (2010)
The concept of recognition has always had an important role in practical philosophy, however we must consider that, except for Hegel, only in recent years political debates and claims of various social movements for recognition have imposed the need to put in the forefront of philosophical reflection the concept of recognition. This is attested by the impact of the precursory essay of Charles Taylor Multiculturalism and " the politics of recognition", the debate between Axel Honneth and Nancy Fraser on the relationship between recognition and redistribution or the attempts of Seyla Benhabib to offer convincing answers to the challenges of multiculturalism from an ethics of discourse, to mention a few examples. Our interest will be focused on the contribution of Paul Ricoeur to the debate on the issue of recognition in his latest work The course of recognition. In the third study, Mutual recognition, Ricoeur expresses his debt to Axel Honneth and conceives part of the development of its position as a dialogue with his work The Struggle for Recognition. Although certain agreements can be established between the two authors, Ricoeur's main critique to Honneth has to be with the idea of struggle as a demand for affective, juridical and social recognition, because in its more conflictive version this idea is in danger of becoming an incessant demand, giving way to bad conscience, victimization and unreachable goals. To avert this Ricoeur proposes to take into account the actual experiences of what he calls "states of peace", conceived as "peaceful experiences of mutual recognition, based on the ceremonial exchange of symbolic gifts". The purpose of this paper will be, first, to reconstruct the terms in which Ricoeur dialogues with the work of Axel Honneth, secondly to evaluate the extent and limits of Ricoeur´s critique to Honneth, and finally to discuss to what extent the ceremonial exchange of symbolic gifts, that in our view constitutes a conciliated position between the philosophy of Husserl and Levinas, far from being an alternative to Honneth´s model can be a complementary proposal.